DIFFERENCES AND SIMILARITIES BETWEEN KOREAN AND UZBEK SUFFIXES - Mamatqosimova Mashhura (Ta'lim innovatsiyasi va integratsiyasi, 2026)
In today’s globalization process, the comparative study of different languages is considered  one  of  the  important  directions  of  linguistics.  Especially,  studying languages that are structurally similar but belong to different language families is of great  scientific  importance.  The  Uzbek  language  belongs  to  the  Turkic  language family,  while  the  Korean  language  is  considered  an  independent  language. Nevertheless, both languages have an agglutinative nature, which is clearly reflected in their grammatical systems. The relevance of this research lies in identifying the similarities and differences between  the  suffix  systems  of  Korean  and  Uzbek  languages  through  comparative analysis,  thereby  facilitating the  language  learning process  and  enriching  linguistic knowledge. The aim of the study is to determine the functional and structural features of suffixes in Korean and Uzbek languages and to analyze them comparatively.